2016
DOI: 10.1177/0394632015623794
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes in expression of IL-4/IL-13/STAT6 pathway and correlation with the selected clinical parameters in patients with atopic asthma

Abstract: Our data support the role of Th2 cytokines (IL-4, IL-13) and STAT6 in Th1/Th2 imbalance and highlight the etiological relationship between IL-4/IL-13/STAT6 signaling and atopy and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
5
17
1
Order By: Relevance
“…Supporting our findings, Bao et al [20], Shi et al [21], Wu et al, [22] and Nesi et al [23] revealed a significant increase in IL-4 in ovalbumininduced asthmatic mice compared to the control. Our finding may also be reinforced in the light of observations of Antczak et al [5] who found higher mRNA level of IL-4 and IL-13 genes in asthmatic patients when compared to controls. But they did not find statistically significant differences between controlled and uncontrolled bronchial asthma, even the highest IL-4 expression was recognized in uncontrolled atopic asthma patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Supporting our findings, Bao et al [20], Shi et al [21], Wu et al, [22] and Nesi et al [23] revealed a significant increase in IL-4 in ovalbumininduced asthmatic mice compared to the control. Our finding may also be reinforced in the light of observations of Antczak et al [5] who found higher mRNA level of IL-4 and IL-13 genes in asthmatic patients when compared to controls. But they did not find statistically significant differences between controlled and uncontrolled bronchial asthma, even the highest IL-4 expression was recognized in uncontrolled atopic asthma patients.…”
Section: Discussionsupporting
confidence: 85%
“…Many family studies, through genome-wide linkage studies, confirmed the involvement of genetic predisposition in the development of atopy in asthmatic patients [4]. The elevated IgE production in asthmatic patients results in promotion of acute hypersensitivity responses, chronic eosinophil-predominant allergic inflammation with T helper-2 (Th2) cells cytokine production [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In asthma, Th2-related cytokines such as IL-4 [3537], IL-5 [38], and IL-13 [35,37] significantly increase; the development of antibodies against Th2-related cytokines is an active field of research [39]. Changes in Th17 cells correlate with asthma induction, making it important to analyze Th-17 proteins such as TNF-α, IL-6, and IL-1β [40].…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of IL-4 principally comprises increasing B cell major histocompatibility complex class II molecule expression, promoting resting B cell FceR expression, elevating secretion of IgE and IgG1 in the activation of B cells, and stimulating IgG to IgE class switching in an autocrine manner to facilitate the differentiation of Th2 cells, while inhibiting Th1 cell proliferation and the Th1 response (Antczak et al, 2016;Pattnaik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%